Review: Advancements and application of immunosensors in the analysis of food contaminants - MD. SHOFIUL AZAM; MD. RAMIM TANVER RAHMAN; ZAIXIANG LOU; YUXIA TANG; SALEH MUHAMMED RAQIB; JAKIA SULTANA JOTHI (Nusantara Bioscience, 2014)
Azam MS, Rahman MRT, Lou Z, Tang Y, Raqib SM, Jothi JS. 2014. Advancements and application of immunosensors in the analysis of food contaminants. Nusantara Bioscience 6: 186-195. Immunosensors are affinity ligand-based biosensor solid-state devices in which the immunochemical reaction is coupled to a transducer. The fundamental basis of all immunosensors is the specificity of the molecular recognition of antigens by antibodies to form a stable complex. This is similar to the immunoassay methodology. Immunosensors can be categorized based on the detection principle applied. The main developments are electrochemical, optical, and microgravimetric immunosensors. In contrast to immunoassay, modern transducer technology enables the label-free detection and quantification of the immune complex. The analysis of trace substances in environmental science, pharmaceutical and food industries is a challenge since many of these applications demand a continuous monitoring mode. The use of immunosensors in these applications is most appropriate. Food chemists should take advantage of immunosensors in food and clinical diagnostics. There are many recent developments in the immunosensor field which have potential impacts. The future role of this technique in intra-laboratory, as well as bedside testing, will become even more important as the food laboratory is faced with increasing pressure to contain costs. Objective of this paper is to give a general overview of the possible application of immunosensors to the food analysis field.